2007
DOI: 10.4000/quaternaire.1014
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, ecology and biochronology of herbivore associations in Europe during the last 3 million years

Abstract: Evolution, ecology and biochronology of herbivore associations in Europe during the last 3 million years Évolution, écologie et biochronologie des associations d'herbivores en Europe sur les 3 derniers millions d'années

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…3, Table 3). According to Guérin [81], Agustí and Antón [64] and Brugal and Croitor [82], G. meneghini was a mixed feeder with a robust skeleton and short limbs adapted to locomotion on mountainous uneven areas similar to modern gorals from Asia. Fakhar-i-Abbas et al [83] studied the feeding preferences of the gray goral and found out that it relies mainly on grasses, although it can browse too; this is in agreement with our G. meneghini δ 13 C values situated towards the high cut-off for open woodland and mesic C 3 grassland.…”
Section: Resultsmentioning
confidence: 99%
“…3, Table 3). According to Guérin [81], Agustí and Antón [64] and Brugal and Croitor [82], G. meneghini was a mixed feeder with a robust skeleton and short limbs adapted to locomotion on mountainous uneven areas similar to modern gorals from Asia. Fakhar-i-Abbas et al [83] studied the feeding preferences of the gray goral and found out that it relies mainly on grasses, although it can browse too; this is in agreement with our G. meneghini δ 13 C values situated towards the high cut-off for open woodland and mesic C 3 grassland.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there is only scant and unconvincing evidence that this species, which had been defined on the ground of morphological features of skull and horn-cores from the Early to the early Middle Pleistocene (ca. 1.2-0.5 Mya), survived up to the Late Pleistocene [47,48]. These two considerations prompted us to revisit the osteometric measurements of bison bones from the Early Pleistocene to modern times in order to evaluate whether it was possible to identify morphological changes that remained unidentified or poorly established up to now.…”
Section: Morphometric Analysis Of Bison Metapodialsmentioning
confidence: 99%
“…36.4 kya and carrying a Bb1 mitotype belonged to B. schoetensacki and thus that this mitotype was characteristic of this species [12]. B. schoetensacki, however, is an early Middle Pleistocene species and there are no robustly assigned specimens later on [47,48]. To explore whether there were similarities between B. schoetensacki samples and the Late Pleistocene samples harboring the Bb1 mitotype, we compared morphometric measurements of their metacarpals ( Figure 4B).…”
Section: Morphometric Analysis Of Bison Metapodialsmentioning
confidence: 99%
“…In Northern Eurasia, a major herbivore turnover between 2.6 and 2.2 Ma represents the emergence of the Palearctic zoogeographical province. It is characterized by the appearance of large modern ruminants and was driven by aridity as well as overall cooling and seasonal contrasts in temperature (Brugal and Croitor, 2007) that led to an opening of the landscape. The evolution of hominins and notably the emergence of the genus Homo between c. 2.6 and 2.45 Ma (Deino et al, 2006;Prat, 2007) were probably driven by the extreme climatic fluctuations at this time (Deino et al, 2006).…”
Section: Continental Recordsmentioning
confidence: 99%